Outcomes of Therapeutic Artmaking in Patients Undergoing Radiation Oncology Treatment: A Mixed-Methods Pilot Study. (April 2020) - Kaimal, Girija; Carroll-Haskins, Katrina; Mensinger, Janell L.; Dieterich-Hartwell, Rebekka; Biondo, Jacelyn; Levin, William P.
A cancer diagnosis can be extremely stressful and life-altering for patients. Chronically high levels of stress can increase inflammation and affect the progression of the cancer. Psychosocial interventions could reduce stress and address cancer patients' emotional, psychological, and spiritual needs. This mixed-methods pilot study compared 2 single-session arts-based approaches for patients in active radiation treatment in a large urban hospital. Participants were assigned to either the active control of independent coloring or the therapeutic intervention of open studio art therapy. Participants completed pre-session and post-session saliva samples and standardized psychosocial measures of stress, affect, anxiety, self-efficacy, and creative agency. Both conditions significantly increased participants' positive affect, self-efficacy, and creative agency, and decreased negative affect, perceived stress, and anxiety. No changes of note were seen in the salivary measures. Participants' narrative responses corroborated the quantitative findings and highlighted additional benefits such as supporting meaning-making and spiritual insights. Both arts-based interventions can support the emotional, psychological, and spiritual needs of cancer patients while each has features that may be more suited to the needs of certain patients. Further replication of these findings could support our initial findings that suggest that patients could benefit from having art studio spaces with art therapists and choices of art materials available on the oncology unit.